2018
DOI: 10.1080/1369183x.2018.1429901
|View full text |Cite
|
Sign up to set email alerts
|

Integration of humanitarian migrants into the host country labour market: evidence from Australia

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
(44 reference statements)
1
34
0
Order By: Relevance
“…Finding employment was further compounded by lack of “Oz Experience” and the lack of recognition of previous educational and professional qualifications (Collins and Low, 2010; Delaporte and Piracha, 2018). Financial and language constraints prevented participants from undertaking courses that would enable them to continue in their previous career paths or choose a preferred option.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding employment was further compounded by lack of “Oz Experience” and the lack of recognition of previous educational and professional qualifications (Collins and Low, 2010; Delaporte and Piracha, 2018). Financial and language constraints prevented participants from undertaking courses that would enable them to continue in their previous career paths or choose a preferred option.…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, a segmented labour market allocates bottom jobs to “racially and culturally” visible migrants regardless of their “human capital” (Nahid and Shamsuddin, 2001; Collins, 2003; Colic‐Peisker and Tilbury, 2006; Gaillard and Hughes, 2014). As a consequence of discrimination, refugees with pre‐migration work experience do not perform better than those without (Delaporte and Piracha, 2018) – a distinct push factor for refugee entrepreneurship (Pio, 2007; Baycan‐Levent and Nijkamp, 2009; Collins and Low, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheng et al (2019) used the first two BNLA survey waves to examine a series of human capital indicators, finding that humanitarian migrants' higher proficiency in spoken English is associated with an increased probability of their labour force participation. Using the first three waves of the BNLA survey data, Delaporte and Piracha (2018) found that English proficiency was associated with access to (stable) employment, the wage/earnings level and the educationoccupation mismatch. Yet these studies did not attempt to identify the underlying causal relationship nor the mechanisms through which English proficiency affects labour market outcomes.…”
Section: Existing Literaturementioning
confidence: 99%
“…Most existing studies on the labour market outcomes of humanitarian migrants in Australia focus on ethnically defined refugee groups or narrowly defined refugee groups, which exclude other humanitarian migrants. Two recent exceptions are Cheng et al (2019) and Delaporte and Piracha (2018), who examined the general relationships between human capital and labour market outcomes using representative panel data of humanitarian migrants in Australia. However, as we will elaborate shortly, these scholars did not examine the underlying mechanisms of these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Most research to date has focused on individual characteristics of refugees or on institutional mechanisms for explaining their LM success (Bakker et al, 2017; Bansak et al, 2018; Bevelander, 2011; Delaporte and Piracha, 2018; Hainmueller et al, 2015; Verwiebe et al, 2018). However, we know little about the efficacy of ALMP for refugees’ LMI (for laudable exceptions, see Lundborg and Skedinger, 2016) and even less about employers’ preferences and whether employers consider ALMP participation an asset on a CV.…”
Section: Theorymentioning
confidence: 99%